Celostno vsebinsko-jezikovno učenje skozi poglobljeno razčlembo akronima CLIL - Burazer, Lara (Vestnik za tuje jezike, 2024)
Because the CLIL approach has become somewhat of a staple in modern Slovenian elementary school English textbooks, the authors of this article address the question of the effectiveness of the traditional fragmentation of learning content on one hand and the integration of language with subject matter on the other. The purpose of the article is to clarify to what extent CLIL actually synthesizes past methodologies into a cross-educational paradigm and thus serves as an alterna-tive, or whether it remains at the level of occasional CLIL inserts, additional activities to enhance the diversity of teaching. The article provides insight into the findings of recent research on the most commonly used English textbooks in Slovenian elementary schools and explores the place CLIL has taken in them. The analytical approach to the topic inevitably touches on numerous and varied definitions of the CLIL approach, discussed in the context of the acronym’s analysis. It compares descriptions and names of related practices that have accompanied CLIL on its jour-ney, including the concepts of immersion in foreign language learning, content-based instruction (CBI), and communicative approaches (CA or communicative language teaching - CLT). It briefly discusses the traditions of bilingual education and language baths, along with many other CLIL companions. The acronym’s individual components (content, language, and (integrated) learning) are thoroughly examined, their effectiveness is outlined and linked to foreign language contexts. Finally, the article encourages systematic and continuous use of the CLIL approach as effective support for language acquisition provided the classroom instruction follows its fundamental prin-ciple of foregrounding the content. It promotes CLIL as a way to incorporate the concept of fusion, while critically highlighting the fundamental values of CLIL methodology as important aspects of effective foreign language teaching.
Keywords: acronym; akronim; CLIL approach; CLIL pristop; context; foreign language classroom; foreign language instruction; kontekst; pouk tujega jezika; Slovenian; slovenski; tujejezični; tujejezikovni